Design of a Circular Economy Model for Corn by-Products - Galuh Eska Mulyanto; Tanto P Utomo; Erdi Suroso; Sri Hidayati; Samsul Rizal (The University of Lampung, 2025)
The waste generated from corn cultivation remains underutilized, necessitating studies on its potential for economic value. The objective of this research was to study the cicular economi model to maximally utilize corn wastes. Corn plant samples were collected from 20 different locations. The corn plants were separated into husks, cobs, grains, leaves, and stems, then weighed to obtain physical data in the form of the percentage weight of each part. The parts of the corn plants were chemically analyzed to determine their cellulose, hemicellulose, lignin, extractable substances, ash content, and C/N ratio. In addition, interviews were conducted to assess the potential for developing derivative products and market prospects. Exponential Comparison Method (ECM) was used to determine which derivative products to be developed within the circular economy model design. The study revealed the dry weight composition of corn plant as follows: husks 6.34%, cobs 7.19%, grains 31.65%, leaves 17.24%, and stems 37.58%. The chemical composition of corn plant was hemicellulose 27.55%, cellulose 29.26%, lignin 11.51%, extractive substances 30.19%, and ash content 1.49%. The C/N ratio values of the corn plant by-products were: husks 49.79, cobs 95.11, leaves 30.99, and stems 56.21. Based on the ECM calculations, silage was selected as the top priority to be developed, with a score of 121,972,607.